Reaction of the pulp of cutters of rats to the power module (Эндодонтия Today, 2020)
In the real research changes in a pulp of cutters of rats on the power module by effort 100 gf/cm, fixed on method Koboyashi for 9 days are studied. It is shown that in these terms influence of a power spring causes structural and functional violations in pulp cages against fall of activity of alkaline phosphatase, quantity calcium-connecting proteins - osteocalcin and annexin V. It coincides with observed expansion of a predentinal zone that testifies to delay of processes of a mineralization of a dentine. At the same time, the revealed differentiation and movement of cages from a preodontoblast layer in odontoblast, reflects compensatory reorganization in response to the used force.